Implementation of Environmental Cost Accounting: A Systematic Literature Study and Its Impact on Corporate Profitability - Sofia, Khalida; Fauzia, Nasihah; Nasim, Arim (Invoice : Jurnal Ilmu Akuntansi, 2024)
The role of accounting as a provider of financial information for stakeholders is very important, especially for strategic decision making and policy. Environmental cost accounting is present as an answer to government policies on hazardous waste management for each industry. This study aims to analyze the application of environmental cost accounting. This study uses the SLR (Systematic Literature Review) method as its research approach, which is a systematic approach to reviewing and analyzing the relevant literature available in a particular research domain. In this study, this method involves the identification, evaluation, and interpretation of relevant previous studies in order to achieve the research objectives. The studies were obtained from the Google Scholar database with a time span of the last 10 years, namely from 2013 to 2023. The results of the research conducted by the researcher show that the impact influenced by the application of environmental cost accounting has a positive impact on acceptance and shows the environmental accounting information system model at PGN, on social responsibility, waste management, affects the company's profit, and also on the stock market.